Ética em pesquisa na área das ciências sociais e humanas: um estudo na Universidade Federal de Santa Maria - Minato, Elaide Teresinha Hundertmarck (2014)
The globalized postmodern world is marked by sharp contrasts arising notably in respect of people s dignity indifferent of the places they inhabit. A continuous increase in the level of requirements aiming at protecting participants in the conduct of research in all fields of knowledge involving human beings is symptomatic, especially in democratic societies. From this viewpoint, research ethics is conceived as a new field of knowledge linking different insights. The objective of this study was to study the concepts of professor researchers in the field of social sciences and humanities at Federal University of Santa Maria (UFSM) on research ethics. The research consisted of an exploratory study with quantitative approach, using a questionnaire in order to obtain the quantitative descriptive survey of opinions of researchers about ethical issues in social sciences and humanities. Our research covered a total of 143 faculty researchers working in 13 different graduating programs at the Center of Social Sciences and Humanities (CCSH) area, involving variables related to the following constructs: Profile of the researchers; Conception regarding Ethics on Human Research; Conception on the need for approval of the Ethics and Research Committee (CEP) in CCSH area; Interest and ease in seeking information regarding Research Ethics. A return rate of 32.5% was obtained in-between results, and a predominance of researchers who do not show a clear conception regarding the ethics in this type of research was observed. It was also evident that most of the participants understood that the submission of projects to the CEP is optional in the field of social sciences and humanities. We have also observed that a significant portion of respondents have never had any interest in seeking information on research ethics, implying that the conception of the subject among researchers is limited; yielding thus a gap that may require hard work to promote, provoke and foment discussion on ethical issues. This discussion may contribute to an effective raising of awareness taking advantage of ethical principles in research involving humans in this area.